Proses Pack Nitriding dengan Variasi Suhu dan Media Pupuk Nitrogen Terhadap Kekerasan AISI 420 - Sulistyo, Erwin; Setyarini, Putu Hadi; Sudana, Yoni (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2010)
The aim of this research was to investigate the effects of heating temperature and concentration of nitrogen fertilizer, i.e urea and ZA, during pack nitriding to the surface hardnessof AISI 420. The process was done by heating the steel of AISI 420 with temperature varied between 4200C, 4700C, 5200C, 5700C dan 6200C for 6 hours after stress relieving in the pack fulfiled with urea or ZA. The result measured by microvickers hardness tester showed that the hardness increased as the function of the temperature.Keywords : pack nitriding, temperature, hardness, AISI 420, nitrogen fertilizer